A Focused Group Human Volunteer Study on the Efficacy of a Novel Candyceutical Sleep Aid: “Restore Your Sleep" (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Sleep disorders affect a significant portion of the population and often lead to detrimental health outcomes. Traditional sleep aids, such as melatonin supplements, though widely used, come with potential side effects and risks of dependency. Caim by Arelang Naturals Private Limited, renowned for their commitment to health and well-being developed “Restore Your Sleep”- a Non melatonin dark chocolate enriched with herbal extracts including Nutmeg, Walnut, St. John's Wort, Passion flower, and Valerian for promoting restorative sleep and overall vitality. So, a focused group observational human study was conducted on 75 participants for 15 days to evaluate effectiveness of the chocolates for restorative sleep. The evaluation was done using Leeds Sleep Evaluation Questionnaire (LSEQ) and analyzed using t-test. Focused group trial results showed significant improvements in sleep quality parameters, including increased sleep duration and reduced sleep onset latency, in the treatment group.